FRI0296 Level of confidence in the diagnosis of spondyloarthritis by expert readers in sacroiliac joint MRI: a new gold standard criterion for defining a positive MRI?. (23rd January 2014) - Weber, U.; Rufibach, K.; Lambert, R.G.; Ostergaard, M.; Chan, S.; Zubler, V.; Pedersen, S.J.; Maksymowych, W.P.
Abstract : Background: Defining a positive MRI in early axial spondyloarthritis (SpA) requires a gold standard criterion for the diagnosis of SpA and is typically based on clinical findings because structural changes on pelvic radiographs may take more than 10 years to become apparent. However, clinician expert opinion as gold standard has inherent limitations leading to false positive or negative assignments and requires lengthy follow up to ascertain development of radiographic sacroiliitis. Level of confidence in the diagnosis of SpA according to expert global assessment of sacroiliac joint (SIJ) MRI may constitute a candidate gold standard criterion for defining a positive MRI in non-radiographic axial SpA (nr-axSpA). Objectives: (1) To assess the inter-reader reliability of the level of confidence in the diagnosis of SpA according to expert global assessment of SIJ MRI; (2) To compare this MRI-based criterion with clinician expert opinion. Methods: The study population comprised 220 consecutive patients with back pain ≤50 years old newly referred to 2 university clinics, and 79 healthy controls. Patients were classified by clinical examination and pelvic radiography as having nr-axSpA (n=74), ankylosing spondylitis (n=60), or mechanical back pain (n=86). SIJ MRI were assessed in random order by 4 blinded expert readers according to a standardized module. Readers recorded their level of confidence in the diagnosis of SpA by global evaluation of the MRI scan on a 0-10 scale (0 = definitely not SpA; 10 = definite SpA). Assignment of a definitive diagnosis of SpA was pre-specified as the majority (at least 3 of 4) of readers recording definite SpA with a confidence level of 8-10. Absence of SpA required all 4 expert readers to record non-SpA (≤4 on 0-10 scale). We calculated the inter-reader agreement for a diagnosis of SpA or non-SpA according to these confidence level cut-offs on global SIJ MRI assessments, and we compared this MRI-based criterion with clinician diagnosis, both by percentage agreement and kappa statistics. Results: The mean percentage agreement among 6 reader pairs for a diagnosis of SpA/non-SpA according to global SIJ MRI was 92.0% and the mean kappa 0.83. Kappa for agreement regarding level of confidence in the diagnosis of SpA by all 4 readers was excellent (0.83; CI 0.78-0.88). Conclusions: Level of confidence in the diagnosis of SpA according to expert global assessment of SIJ MRI by expert readers may constitute a candidate gold standard criterion for defining a positive MRI in nr-axSpA. This alternative to clinician expert classification deserves further validation in other inception cohorts of early SpA patients. Disclosure of Interest: None Declared